Hyperimmune Bovine Colostral Anti-CS17 Antibodies Protect Against Enterotoxigenic Escherichia coli Diarrhea in a Randomized, Doubled-Blind, Placebo-Controlled Human Infection Model. (21st March 2019) - Savarino, Stephen J; McKenzie, Robin; Tribble, David R; Porter, Chad K; O'Dowd, Aisling; Sincock, Stephanie A; Poole, Steven T; DeNearing, Barbara; Woods, Colleen M; Kim, Hye; Grahek, Shannon L; Brinkley, Carl; et al.
Abstract: Background: Enterotoxigenic Escherichia coli (ETEC) commonly cause diarrhea in children living in developing countries and in travelers to those regions. ETEC are characterized by colonization factors (CFs) that mediate intestinal adherence. We assessed if bovine colostral IgG (bIgG) antibodies against a CF, CS17, or antibodies against CsbD, the minor tip subunit of CS17, would protect subjects against diarrhea following challenge with a CS17-expressing ETEC strain. Methods: Adult subjects were randomized (1:1:1) to receive oral bIgG against CS17, CsbD, or placebo. Two days prior to challenge, subjects began dosing 3 times daily with the bIgG products (or placebo). On day 3, subjects ingested 5 × 10 9 cfu ETEC strain LSN03-016011/A in buffer. Subjects were assessed for diarrhea for 120 hours postchallenge. Results: A total of 36 subjects began oral prophylaxis and 35 were challenged with ETEC. While 50.0% of the placebo recipients had watery diarrhea, none of the subjects receiving anti-CS17 had diarrhea ( P = .01). In contrast, diarrhea rates between placebo and anti-CsbD recipients (41.7%) were comparable ( P = 1.0). Conclusions: This is the first study to demonstrate anti-CS17 antibodies provide significant protection against ETEC expressing CS17. More research is needed to better understand why anti-CsbD was not comparably efficacious. Clinical Trials Registration . NCT00524004